2009
DOI: 10.1074/jbc.m109.049809
|View full text |Cite
|
Sign up to set email alerts
|

Fibril Fragmentation Enhances Amyloid Cytotoxicity

Abstract: Fibrils associated with amyloid disease are molecular assemblies of key biological importance, yet how cells respond to the presence of amyloid remains unclear. Cellular responses may not only depend on the chemical composition or molecular properties of the amyloid fibrils, but their physical attributes such as length, width, or surface area may also play important roles. Here, we report a systematic investigation of the effect of fragmentation on the structural and biological properties of amyloid fibrils. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
419
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(469 citation statements)
references
References 47 publications
39
419
4
1
Order By: Relevance
“…Because these are known to be reactive sites, the above observations suggest a role for fibril ends in amyloid-lipid interaction and possibly in amyloid pathogenesis (23,24,27). Fragmented fibrils of all three proteins were also found to induce dye leakage from negatively charged liposomes, the most susceptible of which contain a mixture of the cellular lipids phosphatidylcholine (PC) and phosphatidylglycerol (PG), but liposomes with a variety of compositions were damaged by the fibrils in all cases (27).Here, we use β 2 m amyloid fibrils formed in vitro as a model system to investigate the structural basis of membrane damage by amyloid fibrils (27, 28). Previous studies have shown that these fibrils possess a parallel in register cross-β structure (29, 30) assembled into multidomain filaments coiled together, described by cryo-EM (28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because these are known to be reactive sites, the above observations suggest a role for fibril ends in amyloid-lipid interaction and possibly in amyloid pathogenesis (23,24,27). Fragmented fibrils of all three proteins were also found to induce dye leakage from negatively charged liposomes, the most susceptible of which contain a mixture of the cellular lipids phosphatidylcholine (PC) and phosphatidylglycerol (PG), but liposomes with a variety of compositions were damaged by the fibrils in all cases (27).Here, we use β 2 m amyloid fibrils formed in vitro as a model system to investigate the structural basis of membrane damage by amyloid fibrils (27, 28). Previous studies have shown that these fibrils possess a parallel in register cross-β structure (29, 30) assembled into multidomain filaments coiled together, described by cryo-EM (28).…”
mentioning
confidence: 99%
“…The end surfaces of fibrils (herein termed "fibril ends") are unusually reactive entities: they play a key role in catalyzing recruitment and conformational conversion of amyloid-forming proteins (23, 24) and provide the sites for templated elongation of amyloid fibril growth (25, 26). Recently, Xue et al (27) showed that short fibrils of β 2 -microglobulin (β 2 m), α-synuclein, and hen lysozyme, each prepared by fragmentation of longer fibrils, cause increased damage to membranes and disruption to cellular function compared with the initial long fibrils. Short and long fibril preparations differ in the number of fibril ends at a given protein concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 At the same time, different fibril morphologies can result in different degrees of toxicity 3 and fibril fragmentation can enhance amyloid cytotoxicity. 4 Thus, detailed knowledge about the structure of amyloid fibrils is required to obtain insight into the toxicity of protein aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Stirring and shaking protein samples during aggregation can affect amyloid fibril formation and change the properties of the resulting aggregated species [13]. Therefore, we next examined the aggregation properties of Arctic and Rescue under conditions in which the samples were shaken.…”
Section: Characterization Of the Aggregation Process For Arctic And Rmentioning
confidence: 99%